Gastrodiplomacy and business climate enhancement in ASEAN: Thailand’s Global Thai Initiative and Malaysia’s Malaysia Kitchen programme - Akhdiat Dimas Abimanyu (Priviet Social Sciences Journal, 2026)
Gastrodiplomacy is a form of cultural diplomacy that utilizes culinary arts as a soft power instrument to build a country's image while simultaneously encouraging economic growth and tourism. In the ASEAN region, gastronomy is increasingly viewed as strategic, as reflected in the 2018 Joint Declaration on Gastronomy Tourism. This article analyze the role of gastrodiplomacy in improving the business climate in ASEAN through a comparative study of Thailand's Global Thai program and Malaysia's Malaysia Kitchen Programme. This research uses a qualitative approach with comparative methods based on literature review. The results show that Global Thai emphasizes culinary authentication and standardization through certification and strengthening global restaurant networks, which impacts culinary business expansion and increased tourism. Meanwhile, the Malaysia Kitchen Programme adopts a more adaptive approach through financial support, cross-sector collaboration, and an emphasis on halal cuisine and multiculturalism, which are effective in strengthening the business ecosystem. This study concludes that gastrodiplomacy functions not only as a cultural promotion but also as a contextual and relevant economic diplomacy strategy for ASEAN countries.